Translocated populations are genetically similar to natural populations and populations resulting from natural colonizations - José F. Meléndez-Cal-y-Mayor; Jasmin Winkler; Ramon Müller; Beatrice Lüscher; Janine Bolliger; Arpat Ozgul; Benedikt R. Schmidt (PLoS ONE, 2026)
Genetic diversity and structure are rarely assessed in populations established through conservation translocation. Here, we analysed the genetic structure and diversity of populations of an endangered pond-breeding amphibian, the common midwife toad, Alytes obstetricans , by comparing translocated populations against two types of populations: (i) populations which have recently colonized newly created ponds and (ii) natural populations which have been known to be present for a long time. Bottleneck events and dispersal patterns were analysed to describe the outcome of the translocations. In addition, we simulated trajectories of genetic diversity (H e ) of populations over time. The genetic diversity of natural colonized and translocated populations was similar to that of natural populations. However, there were signatures of genetic bottleneck events in three colonized populations and in a natural population. Simulations of genetic diversity over time showed that number and frequency of dispersers and population size are important parameters determining genetic diversity in the populations in the future. We conclude that, translocated, natural and colonized populations are genetically comparable, indicating that translocations can serve as an effective tool in conservation efforts. However, constructing ponds and waiting for natural colonization is also known to work well.